Construction of Optically Active Quaternary Propargyl Amines by Highly Enantioselective Zinc/BINOL‐Catalyzed Alkynylation of Ketoimines. Issue 36 (15th July 2013) - Huang, Gaochao; Yin, Zengsheng; Zhang, Xingang
Abstract A general and efficient method for the highly enantioselective alkynylation of ketoimines through a zinc/1, 1′‐bi‐2‐naphthol (BINOL)‐catalyzed process has been developed. A variety of ketoimines, including α‐fluoroalkyl α‐imine esters, α‐aryl α‐imine esters, and trifluoromethyl aryl ketoimines, are applicable and provide their corresponding quaternary propargyl amines in excellent yields with high ee values (up to 99 % ee). Both the steric and electronic effects of substituents at the 3, 3′ positions of BINOL are critical for the reaction efficiency and enantioselectivity. To demonstrate the usefulness of the method, (R)‐α‐CF3 α‐proline has been prepared in a highly efficient manner. The notable features of this protocol are its broad substrate scope, high reaction efficiency (up to 99 %) and enantioselectivity (up to 99 % ee), low catalyst loading (5 mol % of BINOL derivative), and mild reaction conditions.